Implikasi Penerapan Karantina Wilayah Akibat Wabah Penyakit Berbasis Peraturan Perundang-Undangan - Veri Mei Hafnizal; ilham khalid (Jurnal Transformasi Administrasi, 2020)
The spread out of a disease is a form of disaster which include into the category of non-natural disasters. The Ministry of Health has responded by realising various types of guidelines and protocols into form of guidelines, prevention methods, and other technical regulations. This research is a qualitative research with the approach method taken in this research is normative juridical approach through literature study. Qualitative research is a research which produces descriptive data in the shape of speech or writting and the observed of people behavior. The data which is obtained in this study are secondary data which comes from a number of books, articles, journals, mass media and electronics. The writing method uses analytical descriptive which describe and discuss comprehensively to find out the effectiveness of the Government Regulation Number 21 Of 2020 About Large Scale Social Distancing In Order To Acceleration in Resolving Corona Virus Disease (PP PSBB) is legitimated in the community and the government itself. The enactment of PP PSBB has legal consequences that have not been accomodate in order to the side of legal base umbrella it self. Some conditions require more specific technical regulations so that the primary regulation could be run. Thus, it could be stated that the system of regulation and the umbrella law in handling the abnormal conditions is not optimal. There is claim from the central government to the regional government that has to work together in order to to face the covid19. It reflected that there are certain terms and conditions in determining an area for the implementation of PSBB.